Profissionalismo médico: desenvolvimento de um instrumento de avaliação do médico residente - ANDRADE, R. A. (2018)
Objective: To develop and adapt an instrument for the evaluation of Professionalism in medical residents of the University Hospital Alzira Velano. Methodology: This study is characterized as non-experimental, transversal, quantitative, divided into 2 phases: Adaptation and Application of a methodologically based instrument (Based on the evaluation and the certification examination of the residents of the Family Medicine of Canada) to measure professionalism physician in the resident doctors of the University Hospital Alzira Velano, aiming to evaluate their degree of professionalism, comparing the variables gender, age group, year of residence and academic performance. This questionnaire was applied to 2 preceptors of each clinic for answers about each resident and the relevance of the questions in the context of medical professionalism. Results: Under the reliability analysis in the application of both preceptors, we obtained a high Cronbach's alpha index. We did not obtain significant difference in relation to sex, age group, year of residence and academic performance. In the analysis of conglomerates, we obtained 3 different groups (minor, intermediate and higher professionalism) that did not present significant difference in the correlation with the academic performance. Conclusion: The scale of evaluation of professionalism showed a high internal consistency, but with highly correlated items. The factors of gender and age did not show a significant difference in the degree of medical professionalism, as well as the year of residence. There was no correlation between academic performance and the degree of statistically significant professionalism. More studies will be necessary, with a higher "n", to determine their use in undergraduate contexts and to study the associations of students' attitudes towards professionalism.